Crenças e motivação em contexto de língua estrangeira para a terceira idade: subsídios para o desenvolvimento de competências do professor - Scopinho, Raquel Albano (Universidade Federal de São Carlos, 2014)
The teaching-learning process of a foreign language for the Third Age is a theme that demands attention and has been little explored. Through the investigation of beliefs and motivational aspects in such a context, we intend to provide subsidies for the development of teachers competences, especially the ones who are involved with the referred public. By having in mind that this issue demands knowledge of the real changes that occur during the process of ageing, we have sought support in the fields of Gerontology, Sociology, Psychology and Applied Linguistics itself. The theoretical framework of this thesis was based upon Neri (1991, 1993, 1995, 2000), for the issues related to the Third Age; Dörnyei (1994, 2001, 2005), for the motivational aspects; Barcelos (2001, 2004), for the beliefs, and Almeida Filho (2002, 2005, 2012), for the competences. The research was developed through several instruments such as questionnaires, interviews and self-reports, which involved 110 participants. The analyzed data show us some aspects to be considered in the conduction of the teaching-learning process. We have to consider the single characteristics of the Third Age public, so that we can be aware of the benefits of a social and cognitively exciting environment for the development and maintenance of the elderly physical and mental capacities. However, to achieve this awareness, it is necessary to overcome some possible stereotyped and prejudiced ideas or images of the old people and the old age that are current in society, especially when it refers to the beliefs that old people are not able to acquire a foreign language, that while getting older, we start losing memory gradually and that the elderly do not feel motivated to the acquisition of knowledge or the acquisition of another language anymore.
Keywords: Linguística; Material didático; Língua estrangeira; Terceira idade; Crença; Motivação; Competências; Third age; Foreign language; Belief; Motivation; Competences; LINGUISTICA, LETRAS E ARTES::LINGUISTICA